SOSIALISASI LITERASI DAN LEMBAGA KEUANGAN SYARIAH PADA MASYARAKAT DESA SUKABUNGAH - Aulia, Salwa Afronisa; Maemunah, Umi Khana; Putra, Purnama; Tirtajaya, Mas Deden (LPPM Universitas Islam 45, 2024)
This community service activity aims to educate the public about sharia finance. The main target of this sharia financial literacy socialization activity is the community in Sukabungah Village, Bojongmangu District, Bekasi Regency. The activities were carried out in the form of seminars by the community service implementation team at Islamic University 45 Bekasi. from the results of observations and interviews, the existence of Bank Emok (Lentenir) in Sukabungah Village still exists today, this is proven by the fact that 60% of the community is ensnared by loan sharks and even online loans (pinjol) this occurs because of the lack of understanding of the people of Sukabungah Village regarding sharia finance. . Therefore, in Community Service activities, the service team plans to carry out outreach through seminars related to sharia finance. After holding sharia finance socialization activities through seminars, the Sukabungah village community gained new knowledge about sharia finance, thereby increasing knowledge and information about sharia finance, managing and managing finances well and being aware of the negative effects of using loan sharks and interest-bearing loans.